Die Beziehung zwischen dem Wettbewerbsrecht und dem Recht geistigen Eigentums: Konflikt, Harmonie oder Arbeitsteilung? - Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2006)
Die Beziehung zwischen dem Wettbewerbsrecht und dem Recht geistigen Eigentums gilt seit jeher als problematisch. Für viele ist sie inhärent konfliktär. Während das Wettbewerbsrecht darauf gerichtet sei, Marktmacht zu zerstören, bestehe der Zweck des Rechts geistigen Eigentums wie z. B. des Patentrechts, Urheberrechts und Markenschutzrechts darin, Marktmacht zu schaffen. Vertreter der Konfliktthese gestehen zwar zu, daß beide Rechtsmaterien der Förderung der ökonomischen Wohlfahrt dienen, aber sie tun dies angeblich doch in verschiedener Weise. Ihrer Ansicht nach ist das Wettbewerbsrecht eher myopisch und kurzfristig orientiert. Es fördere Praktiken, die die Preise in Richtung Grenzkosten treiben und überdurchschnittliche Gewinne beseitigen, und es bekämpfe Praktiken, die dies verhindern. Ziel sei statische allokative und technische Effizienz. – – The relationship between the Antitrust Law and the Patent, Copyright and other Intellectual Property (IP) Laws has perplexed antitrust scholars and practitioners for a long time. Intellectual property and antitrust regimes both seek to advance the economic well-being of society. However, whereas the IP laws are designed to create exclusive rights - rights that sometimes rise to the level of monopolies - in order to encourage innovation and creativity, Antitrust Law is designed to foster competition and to prevent the formation of monopolies. Finding the right balance between maintaining competition and creating incentives to innovate is no easy task. This paper emphasises a division of labour: IP law should concern itself with assigning and enforcing intellectual property rights, while Antitrust Law should concern itself with the use of those rights for anti-competitive purposes. I develop the main thesis in three parts: The first part of the paper outlines the economics of IP rights. The second part presents basics of Antitrust Law. The third part deals with some specificity of the IP/Antitrust Law interface: Reasons giving rise for special concerns are found in the areas of mergers, licensing and cross-licensing, patent pools, grant-backs, practices to extend the legal patent monopoly beyond the life of the patent, interfaces and interoperability in networks, umbrella branding, and compulsory trademark licensing. The last part of the paper summarises with a set of principles for competition policy.
Keywords: O34; L4; 330; competition policy; competition law; antitrust; intellectual property